2018
DOI: 10.4081/ijwc.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-assisted wound debridement for scleroderma digital ulcers

Abstract: Debridement is a key element of wound care. It involves the removal of devitalized tissue from the wound bed in order to allow wound healing. Microcirculatory ulcers in general and scleroderma ulcers in particular are extremely painful, very reactive and rather unwilling to accept aggressive local treatments of a mechanical type or surgical cleaning which can promote an abnormal phlogistic response with a necrotizing evolution. For the elimination of devitalized tissue is necessary to promote autolytic or enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…67 A recent paper reported that ultrasoundassisted wound debridement reduced pain, necessity of antimicrobial therapy, and healing time in SSc patients. 68 The presence of infection should be carefully investigated during evaluation of the patient with DUs during SSc. Actually, the presence of infection is associated with a higher risk of local complications and reduced healing of DUs.…”
Section: Topical Treatmentmentioning
confidence: 99%
“…67 A recent paper reported that ultrasoundassisted wound debridement reduced pain, necessity of antimicrobial therapy, and healing time in SSc patients. 68 The presence of infection should be carefully investigated during evaluation of the patient with DUs during SSc. Actually, the presence of infection is associated with a higher risk of local complications and reduced healing of DUs.…”
Section: Topical Treatmentmentioning
confidence: 99%